Interface Engineering Between Multi‐Elemental Alloy Nanoparticles and a Carbon Support Toward Stable Catalysts (Adv. Mater. 9/2022). Issue 9 (3rd March 2022) - Li, Tangyuan; Dong, Qi; Huang, Zhennan; Wu, Lianping; Yao, Yonggang; Gao, Jinlong; Wang, Xizheng; Zhang, Haochuan; Wang, Dunwei; Li, Teng; Shahbazian‐Yassar, Reza; Hu, Liangbing
Abstract : Hierarchical Catalysts In article number 2106436, Liangbing Hu and co‐workers report an interface engineering strategy to improve the stability of multi‐elemental alloy (MEA) nanoparticles on a carbon substrate. The MEA‐oxide–carbon hierarchical catalysts synthesized by a rapid high‐temperature shock method demonstrate excellent thermal and electrochemical stabilities, and hold great promise for various catalytic applications.